2023
DOI: 10.3390/sym15020321
|View full text |Cite
|
Sign up to set email alerts
|

Observational Constraints on F(T,TG) Gravity with Hubble’s Parametrization

Abstract: Any new gravitational theories can be built with the help of a gauge theory with local Poincare symmetry. This local Poincare symmetry can set up a space-time with torsion. In the present study, the authors working on the parametrization approach towards Hubble’s parameter in the frame of modified teleparallel Gauss-Bonnet gravity which is established on the torsion invariant T and the teleparallel equivalent of the Gauss-Bonnet term TG, say F(T,TG) gravity. In particular, gravity is responsible for an integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 97 publications
2
1
0
Order By: Relevance
“…On the other hand, SEC is violated throughout the evolution providing the anti-gravitational effect, known to be the dark energy, resulting in the cosmic accelerated expansion. This is in good agreement with [25,26].…”
Section: The Energy Conditionssupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, SEC is violated throughout the evolution providing the anti-gravitational effect, known to be the dark energy, resulting in the cosmic accelerated expansion. This is in good agreement with [25,26].…”
Section: The Energy Conditionssupporting
confidence: 88%
“…evolution resulting in the cosmic accelerated expansion, which is in good agreement with the recent observations [25,26].…”
supporting
confidence: 92%
“…Now we provide a glimpse of the main features of the scale factor (transit scale factor) and derive a few physical quantities from them to discuss the observed scenario. Hence, for the transit scale factor, Hubble's parameter [54,55] is observed as follows:…”
Section: Specific Hubble Parameters and Analysismentioning
confidence: 99%
“…Work [38] discussed classes of exact and perturbative spherically symmetric solutions in modified teleparallel f (T, B) gravity, while in [39] the authors examined the second law of thermodynamics in f (T, B) theory and using cosmological reconstruction technique, showed that some models of f (T, B) can mimic the de-Sitter, power-law and ΛCDM models. Analysis of the Tsallis holographic dark energy and energy conditions in teleparallel f (T, B) gravity theory were considered in [40,41].…”
Section: Introductionmentioning
confidence: 99%